Alterações auditivas e qualidade de vida em sujeitos com disfunção temporomandibular - Lima, Jully Anne Soares de (2016)
INTRODUCTION: Temporomandibular disorder (TMD) are characterized by a set of signs and symptoms that can affect the muscles, temporomandibular joints (TMJ) and associated structures, with prejudice to the quality of life of patients. Symptoms such as tinnitus, ear fullness or vertigo are very common in these patients, but the real relationship between those entities is not fully understood. OBJECTIVE: Describe the relationship of TMD, hearing complaints and audiological condition of patients with TMD and possible compromises on the quality of life of the subjectsMETHODS: A cross-sectional study was conducted with two groups: TMD and tinnitus (25 subjects - TMD group) and healthy control without TMD (29 subjects - control group). The sample was non-probabilistic nature and obtained by convenience. They were used: a medical history form for evaluation of otologic symptoms and tinnitus, the Oral Health Impact Profile (OHIP-14), the Tinnitus Handicap Inventory (THI) and the Research Diagnostic Criteria for Temporomandibular Disorders (RDC / TMD). For data analysis was performed using Fisher's exact test to compare groups, the Shapiro-Wilk normality test, being used the ANOVA and Tukey's test for normal data, and the MannWhitney U and Kruskal-Wallis test for non-normal data. There was dichotomy of the degrees of disability THI (no / mild and moderate / severe) for association with the domains of OHIP. It was considered significant 95% (a = 0.05). RESULTS: Most of the sample of the case group was female (84%), and had a mean age of 41.6 (± 13.07) years. The most frequent diagnoses were of Group I (myofascial pain with and without opening limitation - 96%) and Group III (arthralgia - 76%64%), and 3 combined diagnostics. Most reported symptoms other than tinnitus was the ear fullness (64%) and dizziness (64%), followed by hearing loss (36%). The frequency of tinnitus appears more in acute (6 kHz to 8 KHz) and medium intensity (15dB and 45dB). The THI averaged 32.12 classifying the sample in moderate impairment. The tritonal average test group are higher than those in the control group (p <0.0001). TDM has a negative impact on quality of life (p <0.001), however the number of diagnoses seemed not to influence. Tinnitus resulted in higher levels of psychological distress measured by OHIP-14 in patients classified as highest level of disability (moderate or severe) by THI. CONCLUSION: The most common type was DTM muscle and arthralgia and those subjects presenting symptoms hearing and tinnitus at higher frequencies and mean intensities. Additionally, when coupled, it negatively impacts the quality of life.